Chondrogenic differentiation of bone marrow‐derived mesenchymal stromal cells via biomimetic and bioactive poly‐ε‐caprolactone scaffolds1. Issue 6 (27th November 2012) - Schagemann, J. C.; Paul, S.; Casper, M. E.; Rohwedel, J.; Kramer, J.; Kaps, C.; Mittelstaedt, H.; Fehr, M.; Reinholz, G. G.
Abstract: The objective of this study was to develop a scaffold for mesenchymal stromal cell (MSC) recruitment, proliferation, and chondrogenic differentiation. The concept behind the design is to mimic the cartilage matrix and contain stimulatory agents that make continuous supply of inductive factors redundant. Nanofibrous (N: ∼400 nm) and microfibrous (M: ∼10 μm) poly‐ε‐caprolactone (PCL) scaffolds were combined with 1% high‐molecular‐weight sodium hyaluronate (NHA/MHA), 1% hyaluronan (HA) and 200 ng transforming growth factor‐beta 1 (TGF‐β1; NTGF/MTGF), or 0.1% bovine serum albumin (N/M). Scaffolds were seeded with MSCs from bone marrow and cultured without growth factors in vitro . Cultures with chondrogenic medium supplemented with TGF‐β1 served as controls. Proliferation, migration, and release of TGF‐β1 were investigated. Cell differentiation was evaluated by polymerase chain reaction (PCR) and real‐time PCR. NTGF and MTGF exhibited primarily an initial release of TGF‐β1. None of the factors released by the scaffolds recruited MSCs. The expression of aggrecan was dependent on the scaffold ultrastructure with nanofibers promoting increasing and microfibers decreasing expression levels. Composites containing HA demonstrated elevated seeding efficiency and lower type I collagen expression. Expression of type II collagen was dependent on continuous or late supply of TGF‐β1, which was not provided by our scaffold design. The initial release of TGF‐β1 induced an expression of type I collagen and osteogenic marker genes. In conclusion, nanofibrous PCL scaffolds with or without augmentation are suitable for chondrogenic initiation of MSCs. Initial release of HA is sufficient in terms of directing the implanted MSCs toward a chondrogenic end, whereas a late release of TGF‐β1 is preferred to foster type II and avoid type I collagen expression. © 2012 Wiley Periodicals, Inc. J Biomed Mater Res Part A, 2013.